Remember me memory and forgetting in the digital age - Sisto, Davide 1978- (Polity Press, 2021)
As the end of December draws near, Facebook routinely sends users a short video entitle 'Your year on Facebook.' It lasts about a minute and brings together the images and posts that received the highest number of comments and likes over the last year. The video is rounded off with a message from Facebook that reads: 'Sometimes, looking back helps us remember what matters most. Thanks for being here.'